IMPROVEMENT OF GREEN ACCOUNTING METHODOLOGY IN UZBEKISTAN: EXPERIENCE OF DEVELOPED COUNTRIES - Khalilov Sherzod Akhmatovich (KONFERENSIYALAR, 2025)
In the contemporary global economic landscape, the integration ofenvironmental considerations into accounting practices has emerged as a criticalfactor for sustainable development. This integration, known as 'greenaccounting', involves the systematic inclusion of environmental assets and theirdepreciation in national and corporate accounting